Catatan Mengenai Perkembangan Akuntabilitas Publik Pada Era Demokrasi di Indonesia - Riyadi Santoso (Program Studi Ilmu Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam '45 (UNISMA) Bekasi, 2012)
Public accountability as accountability to peoples on democracy era in Indonesian very sure will become developing, usually become with civil society growth. Actually, we need look for with take care that its developed still felt so many problems, because democracy transition in this country. Political Parties must have partipation to improvement democracy transition procceses, in the fact still became part of that self problems. Political Parties still internal problems self as, to development images, but on another aspect as fact do not transparency and not accountable. Fact so many candidats, members of political party to doing corruption problems and law cases others from in center level to regional level. This is one of many inconsistency, as euphoria demokracy in Indonesia, but we optimistic that the people and society continous to improve democracy transition process with the powers in the civil society organizations, thats public accountability can to become realy as practice in the future